Analytical Modeling of Development and Implementation of Telecommunication Technologies - Gluhov, Vladimir; Leventsov, Valery; Radaev, Anton; Nikolaevskiy, Nikolay (Internet of Things, Smart Spaces, and Next Generation Networks and Systems, 2018)
The paper discusses the problem of defining the characteristics of processes related to development and implementation of telecommunication technologies. These characteristics must reflect an adequate assessment of expectations for the implementation of new technologies and be a basis for correct and relevant decision-making, which should lead to key competitive advantages, both for an individual enterprise and the economy of the country as a whole. The above circumstances have predetermined the topicality of the research study, whose aim at this stage is to assess the adequacy of the analytical model, which is developed on the basis of Gartner’s hype cycle model and reflects the dependence of expectations for the technology on a time factor. The results of analytical modeling have been obtained on the example of the commonly used telecommunication technology Bluetooth. The source data included a number of articles on the relevant subject from Scopus database. Based on the obtained results, it has been concluded on the working capacity of the used model and recommendations have been given on its possible improvement.